Effectiveness of continuous or bilevel positive airway pressure versus standard medical therapy for acute asthma - Hanekom, Silmara Guanaes (My University, 2008)
ABSTRACT Patients with respiratory failure secondary to acute asthma exacerbation (AAE) frequently present at emergency units. Some patients may develop respiratory muscle fatigue. Current guidelines for the treatment of an AAE center on pharmacological treatment and invasive mechanical ventilation. Noninvasive positive pressure ventilation (NPPV) has an established role in COPD exacerbations. The role it can play in an AAE remains unanswered although it is frequently used in the clinical setting. Aims: The present study proposed to investigate if the early use of NPPV in the forms of continuous positive airway pressure (CPAP) or bilevel positive pressure ventilation (BPPV) together with standard medical therapy in AAE can decrease time of response to therapy compared to standard medical therapy alone. We further tested the effect of BPPV against CPAP. Methods: Asthmatic patients who presented with a severe AAE (PEFR % predicted < 60 %) at the emergency unit were randomized to either standard medical therapy (ST), ST and CPAP or ST and BPPV. Thirty patients fulfilled the inclusion criteria for the study. Groups presented similar baseline characteristics. The mean age for the group was 42.1 ± 12.6 years. Mean baseline PEFR % predicted was 35.2 ± 10.7 % (ST), 30.5 ± 11.7 % (ST + CPAP) and 33.5 ±13.8 % (ST + BPPV). Results: Hourly improvement (Δ) in respiratory rate and sensation of breathlessness was significantly better in the BPPV intervention group. Improvement (Δ) from baseline to end of treatment in respiratory rate and sensation of breathlessness was significant for both CPAP and BPPV (p = 0.0463; p = 0.0132 respectively) compared to ST alone. Lung function was significantly improved in the CPAP intervention group hourly and from baseline to end of treatment (p = 0.0403 for PEFR and p = 0.0293 for PEFR % predicted) compared to ST + BPPV and ST alone. The mean shift (Δ) in PEFR from baseline to 3 hours of treatment was 67.4, 123.5 and 86.8 L/min (p = 0.0445) for ST, ST + CPAP and ST + BPPV respectively. This corresponded to a 38.1, 80.8 and 51.7 % improvement in lung function respectively. Discussion: The effect of BPPV on the reduction of respiratory rate and sensation of breathlessness could be related to the inspiratory assistance provided by BPPV. The significant improvement in lung function in the CPAP group could be related to its intrinsic effect on the airway smooth muscle and / or on the airway smooth muscle load. Conclusion: The present results suggest that adding NPPV to standard treatment for an AAE not only improves clinical signs faster but also improves lung function faster. CPAP seems to have an intrinsic effect on the airway smooth muscle so rendering it more effective in ameliorating lung function.
Keywords: asthma; continuous positive airway pressure CPAP; bilevel positive airway pressure BIPAP; noninvasive positive pressure ventilation NPPV